Prostate cancer stem cells and their targeted therapies - Su, Huilan; Huang, Liqun; Zhou, Jianjun; Yang, Guosheng (Frontiers in Cell and Developmental Biology, 2024)
Prostate cancer (PCa) is the most common malignancy amongst men worldwide.Through androgen receptor signaling inhibitors (ARSIs) treatment, patients eventually succumb to castration-resistant prostate cancer (CRPC). For this, the prostate cancer stem cells (PCSC) as the minor population of tumor cells, which possess the capability of tumour promoting relapse, ARSI resistance, and disease progression, are gaining attention. Therefore, the specific therapy targeting PCSC has been a striking momentum. This study reviewed the identification and characterization of PCSC, PCSC-based putative biomarkers, and summarized their mechanisms of action. We further discussed clinical trials of novel therapeutic interventions focused on PCSC-related pathways, PCSC microenvironment, cutting-edge miRNA therapy, and immunotherapy approaches from mechanistic standpoint. This review hopes to provide an updated insights for PCSC plasticity, the identification of new PCSC biomarkers, and optimized treatments for advanced PCa patients.